Hardness of Welded Al 6082 and Al 8011 Plates by Controlling Tilt Angle of Tool in FSW - Vikram Singh, Chandra; Pachauri, Praveen; P. Dwivedi, S.; Sharma, Satpal (International Journal of Engineering and Technology, 2018)
In this study, aluminum alloy 6082 and 8011 were welded using friction stir welding technique on vertical milling machine. Tool speed, Tool shape and tilt angle of tool are considered as input parameters. In the present study, hardness test was carried out to identify the surface property of welded joint, while bend test was carried out to find out bend behaviour of welded samples. Taguchi design with L9 orthogonal array was employed to obtain optimum input parameters for better hardness. Hardness for Al6082-Al8011 joint is better for triangular tool shape and minimum rpm i.e. 560 rpm as the smoothness of tool and tool rpm increases there is decrement in the hardness. While, hardness for Al6082-Al8011 joint is better for triangular tool shape and 00 tilt angle as the tool smoothen and the tilt angle increases the hardness decreases.Â Â